CEO and board characteristics as determinants of private benefits of control: Evidence from the Russian stock exchange - Irina Berezinets; Yulia Ilina; Alexander Muravyev (Institute for the Study of Labor (IZA), 2011)
This paper investigates whether and how various characteristics of CEOs and corporate boards are related to the severity of corporate governance problems within firms. The latter is proxied by private benefits of control, which we measure for dual class stock firms using the voting premium approach. Our empirical analysis is based on data from Russia and takes advantage of the extreme corporate governance problems in the country, considerable variation in corporate governance practices across firms and over time, and presence of a large and exogenously created (during the process of privatization) group of dual class stock companies. The data are assembled from the RTS, SKRIN and SPARK databases and include over 200 firms observed in 1997-2009, with over 1000 observations in total. Our econometric analysis suggests a quadratic relationship between private benefits of control and CEO ownership with a minimum at about 4% CEO ownership, a positive association between CEO tenure and private benefits, and a quadratic in CEO age with a dip in private benefits at about 52 years of age. There is also a quadratic relationship between private benefits of control and board size, implying the optimality of medium-sized (about 9-10 directors) boards. We find no gender effects on private benefits of control.
urn:nbn:de:101:1-201203016332
Keywords: G34; 330; CEO; corporate board; private benefits of control; dual-class stock firms; Russia; Führungskräfte; Aufsichtsrat; Corporate Governance; Managervergütung; Aktiengesellschaft; Schätzung; Russland